Narrating the Chilean Social Revolt through and against Stigma: The Case of Two Older Women from a Stigmatized Neighborhood. - Álvarez-López, Valentina; Méndez, María-Luisa; Angelcos, Nicolás; Rasse, Alejandra (Latin American Research Review, 2024)
This article explores the workings of social and territorial stigma among residents of an stigmatized neighborhood in Santiago de Chile in the context of nationwide conflict. By attending to the narratives of social organizers, it shows how stigma framed the narratives of the Chilean revolt of October 2019 produced by two female organizers older than fifty years without tertiary education. It argues that, for those with less educational and political resources, stigma can help think through a social conflict by translating broader political issues into everyday life experiences and can both constrain and enable different forms of engagement in the revolt. The narratives were obtained by ethnographic interviews carried out in a broader project of the unfolding of the unrest in Santiago’s peripheries between November 2019 and July 2020.